2014
DOI: 10.2527/jas.2013-6793
|View full text |Cite
|
Sign up to set email alerts
|

The effects of live yeast Saccharomyces cerevisiae on postweaning diarrhea, immune response, and growth performance in weaned piglets1,2

Abstract: The effects of live yeast Saccharomyces cerevisiae (strain CNCM I-4407, 10(10) cfu/g; Actisaf; Lesaffre Feed Additives, Marcq-en-Baroeul, France) on the severity of diarrhea, immune response, and growth performance in weaned piglets orally challenged with enterotoxigenic Escherichia coli (ETEC) strain O149:K88 were investigated. Live yeast was fed to sows and their piglets in the late gestation, suckling, and postweaning periods. Sows were fed a basal diet without (Control; n = 2) or with (Supplemented; n = 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 28 publications
10
61
0
4
Order By: Relevance
“…Post‐weanling diarrhoea is one of the principal problems faced by the pig industry. Trckova et al () studied the effects of live yeast S. cerevisiae on post‐weanling diarrhoea in weaned piglets and found that feeding live yeast S. cerevisiae can significantly reduce the diarrhoea of piglets, which is consistent with our study at 2nd week that Piglets fed brewer's yeast hydrolysed have low diarrhoea score after the LPS challenged.…”
Section: Discussionsupporting
confidence: 89%
“…Post‐weanling diarrhoea is one of the principal problems faced by the pig industry. Trckova et al () studied the effects of live yeast S. cerevisiae on post‐weanling diarrhoea in weaned piglets and found that feeding live yeast S. cerevisiae can significantly reduce the diarrhoea of piglets, which is consistent with our study at 2nd week that Piglets fed brewer's yeast hydrolysed have low diarrhoea score after the LPS challenged.…”
Section: Discussionsupporting
confidence: 89%
“…Decreased diarrhea A combination of phages is needed F4 in experimental PWD [130]. In addition, it was shown that the feeding of pigs with live yeast Saccharomyces cerevisiae enhanced their growth and reduced the duration and the severity of PWD caused by ETEC [131]. It has been demonstrated that the administration of a mixture of two probiotics, Pediococcus acidilactici and Saccharomyces cerevisiae boulardii, in the feed of challenged weaned pigs reduced ETEC: F4 attachment to the ileal mucosa in comparison with the group treated with chlortetracycline and tiamulin [103].…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Indeed, pigs that were challenged with E. coli K88 and fed diets containing a yeast fermentation product have higher concentrations of serum tumour necrosis factor‐alpha, less diarrhoea, higher appetite and decreased adherence of E. coli to the intestinal mucosa than pigs fed an un‐supplemented control (Kiarie et al , ). Likewise, pigs fed on diets supplemented with live yeast and exposed to enterotoxigenic E. coli were observed to have reduced disease‐related stress, reduced diarrhoea scores, reduced duration of diarrhoea, and reduced shedding of E. coli (Trckova et al ). Jiang et al () reported that feeding of live yeast and finely ground live yeast increases serum concentrations of IgA, IL‐2 and IL‐6.…”
Section: Probiotic Yeast For Pigsmentioning
confidence: 99%